The Correlation Between Reproductive Health Literacy and the Prevention of Sexually Transmitted Infections (STIs) in the School Environment - Nimas Ayu Lestari Nurjanah; Tuti Rohani; Desi Aulia Umami (STIKes Budi Luhur Cimahi, 2026)
Sexually transmitted infections (STIs) remain a health problem that mostly occurs among teenagers, partly due to a lack of reproductive health literacy. The school environment has a strategic role in increasing understanding and shaping behavior to prevent STIs among teenagers. The purpose of this study was to determine the correlation between reproductive health literacy and STI prevention in the school environment. This study used a quantitative approach with an analytic descriptive design and a cross-sectional method. The population of this study consisted of all students at the selected school, with a total sample of 202 students selected using a simple random sampling technique. Data were collected using a structured questionnaire that had been tested for validity and reliability, then analyzed using univariate and bivariate analyses with the Chi-square test at a significance level of α = 0.05. The results showed that almost half of the respondents had a low level of reproductive health literacy, while their STI prevention behavior was at an adequate level. The statistical test results showed a significant correlation between reproductive health literacy and STI prevention (p = 0.002). Students with better reproductive health literacy tended to have better STI prevention behavior compared to students with adequate and lower literacy levels. In conclusion, reproductive health literacy is significantly related to the prevention of sexually transmitted infections in the school environment. Therefore, it is necessary to strengthen comprehensive and continuous reproductive health education in schools as an effort to prevent STIs among teenagers.